2012
DOI: 10.1182/blood.v120.21.157.157
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Synthetic High Density Lipoprotein Nanostructures Target the SR-B1 Receptor and Differentially Manipulate Cellular Cholesterol Flux in Lymphoma Cells: A Novel Treatment Paradigm

Abstract: 157 We report a nanoparticle-enabled therapeutic approach to B cell lymphoma using synthetic, high-density lipoprotein nanoparticles (HDL-NP). Like natural HDLs, biomimetic HDL-NPs target scavenger receptor type B-1 (SR-B1), a high-affinity HDL receptor expressed by lymphoma cells. Functionally, and unlike natural HDL, a gold nanoparticle template used to control HDL-NP synthesis enables differential manipulation of cellular cholesterol flux through SR-B1. Recent evidence in lymphoblasts and mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have indicated that analog peptide R4F of oral ApoA-I can bind to amyloid β-protein (Aβ) in the brain, and form a polymer to reduce the accumulation of amyloid protein, thus improve the cognitive ability. Therefore, the R4F is used for the synthesis of HDLs, which can improve the biological utilization of polypeptides in treatment of diseases of the central nervous system (Yang et al., 2012 ).…”
Section: Utilizations Of Slp As Drug Nano-materials Vehiclementioning
confidence: 99%
“…Studies have indicated that analog peptide R4F of oral ApoA-I can bind to amyloid β-protein (Aβ) in the brain, and form a polymer to reduce the accumulation of amyloid protein, thus improve the cognitive ability. Therefore, the R4F is used for the synthesis of HDLs, which can improve the biological utilization of polypeptides in treatment of diseases of the central nervous system (Yang et al., 2012 ).…”
Section: Utilizations Of Slp As Drug Nano-materials Vehiclementioning
confidence: 99%